Child welfare and child well-being new perspectives from the National Survey of Child and Adolescent Well-being - Webb, Mary Bruce (New York ; Oxford : Oxford University Press, 2010)
The chapters in this rich synthesis of National Survey of Child and Adolescent Well-Being data represent thoughtful and increasingly sophisticated approaches to the problems highlighted in the study and in child welfare research in general.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Child welfare -- United States